Nursing Practice Guidelines in China do Need Reform: A Critical Appraisal Using the AGREE II Instrument. Issue 2 (29th January 2016) - Jin, Yinghui; Wang, Yunyun; Zhang, Yao; Ma, Yue; Li, Yan; Lu, Cui; Wang, Wei; Li, Ge; Shang, Hongcai
ABSTRACT: Background: An increasing number of nursing practice guidelines (NPGs) of varying methodological and reporting quality have been issued and published in international journals. Currently, the quality of NPGs in mainland China has not been explored. Objective: To assess the quality of NPGs in China mainland using the AGREE II (Advancing Guideline Development, Reporting and Evaluation in Health Care) instrument. Methods: The authors searched the electronic databases of Chinese Biomedical Literature Database, China National Knowledge Infrastructure, The VIP Database, Wan Fang Database, Chinese Master's Theses Full‐Text Database, China Doctor Dissertation Full‐Text Database, and China Proceedings of Conference Full‐Text Database and the web of China Guideline Clearinghouse for NPGs in China published from the inception of databases to December, 2013. Four independent assessors rated the quality of each guideline using AGREE II. The authors classified NPGs into two types: evidence‐based NPG (EB‐NPG) and consensus‐based NPG (CB‐NPG), and compared their quality. The authors also considered whether the quality of NPGs changed over time. Results: Forty‐two NPGs were appraised. Methodological rigor and reporting of NPGs were poor. Across all guidelines, the appraisers assigned the highest scores to the domain "scope and purpose, " and the lowest scored to the domain of "editorial independence." EB‐NPGs were significantly superior to the CB‐NPGs in the domains of "stakeholder involvement, " "rigor of development, " and "editorial independence." There was no improvement over time for all domains. Linking Evidence to Action: This research found an absence of a systematic guideline development methodology and a tendency to rely on expert opinion in the process of developing NPGs. The readers should consider these flaws and limitations when using recommendations in those NPGs.